1998
DOI: 10.1093/ndt/13.6.1489
|View full text |Cite
|
Sign up to set email alerts
|

Regression of left ventricular hypertrophy in haemodialysis patients by ultrafiltration and reduced salt intake without antihypertensive drugs

Abstract: The results of this uncontrolled retrospective study suggest that good long-term BP control and a decrease of LVM can be achieved by continuous efforts to control hypervolaemia. The decrease in volume may be even more important than pressure reduction to achieve this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 1 publication
5
144
0
1
Order By: Relevance
“…Therefore, it is not easy to separate the effects of preload and afterload factors in the pathogenesis of LVH or even to establish a hierarchy of importance because they are intimately related to each other in ESRD patients. Nevertheless, evidence has accumulated to suggest that volume overload, related to inadequate salt restriction and ultrafiltration, plays a dominant role (33,34 …”
Section: What Are the Likely Pathophysiologic And Pathobiologic Mechamentioning
confidence: 99%
“…Therefore, it is not easy to separate the effects of preload and afterload factors in the pathogenesis of LVH or even to establish a hierarchy of importance because they are intimately related to each other in ESRD patients. Nevertheless, evidence has accumulated to suggest that volume overload, related to inadequate salt restriction and ultrafiltration, plays a dominant role (33,34 …”
Section: What Are the Likely Pathophysiologic And Pathobiologic Mechamentioning
confidence: 99%
“…As these treatment modalities greatly facilitate volume control, it is tempting to ascribe these results to a decrease in blood volume and pre-load. The importance of reversing increased pre-load was illustrated by the report of Ozkahya et al, 7 who showed that reversal of hypervolaemia through reduced dietary salt intake and ultrafiltration caused a reduction in LVH in dialysis patients, even without the use of anti-hypertensive agents. All of the above studies support the importance of a reduction in the left ventricular volume for the regression of LVH.…”
Section: Strict Fluid Volume Control and Lvh In Haemodialysis Patientmentioning
confidence: 99%
“…5 While it has been reported that LVH is mostly persistent and progressive despite anti-hypertensive drug treatment, 6 some studies have shown a remarkable reversal of LVH in ESRD patients treated by strict fluid volume control without drugs. 7,8 The exact pathophysiology of LVH in ESRD patients is unknown, but hypertension, volume overload, anaemia, uraemia and arteriovenous shunts are implicated. 9,10 In patients with systemic hypertension, the development of LVH is thought to be caused by the increased pressure load imposed on the left ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, some authors have accepted heart disease as a usual process for these patients, suggesting that deterioration is inevitably linked to that procedure (14). On the contrary, Charra and Özkahya (15,16) have proven that a precise volume control of HD patients decreases arterial blood pressure, causes regression of cardiac hypertrophy and prolongs survival. This suggests that volume control is not enough in most patents, despite the fact that treating physicians may consider that ''Dry Weight'' (DW) of their patients has been reached.…”
Section: Discussionmentioning
confidence: 99%